Design and Performance of an Innovative Hybrid Constructed Wetland for Sustainable Pig Slurry Treatment in Small Farms - Torrens, Antonina; Folch, Montserrat; Salgot, Miquel (Frontiers in Environmental Science, 2021)
Simple and suitable treatment of swine slurry from small farms is paramount especially in sensitive areas. This paper evaluates the viability of an innovative nature-based technology hybrid system (a Vertical Flow Constructed Wetland followed by a Horizontal Flow Constructed Wetland both planted with reeds – Phragmites australis) to treat swine slurry for further land application or discharge in water bodies with reduced nitrogen impact. Physicochemical parameters, bacterial indicators, surface deposits and biomass inside the filters were monitored. The hybrid configuration offered a dual function for simultaneous solid-liquid separation and biological treatment. Removal of organic matter and suspended solids was very high (> 80 % for SS and > 75 % for COD and BOD5) while the overall nitrogen load removal was 65%, due to the combined nitrification/denitrification processes, thus effectively reducing swine slurry nitrogen content. The influence of temperature and design and operational parameters on the treatment efficiency and the hydraulic behaviour were also studied. The vertical constructed wetland achieved good hydraulic performance with no clogging problems, despite high pollutant loads. Some of the pollutants were retained and mineralized in the surface deposit layer, increasing around 20 cm each year. This organic biosolid layer improved filtration efficiency. The high ammonia contents interfered with the growth of Phragmites australis, while the high concentration of suspended solids and organic matter determine the operation and design to be implemented.